PEMERIKSAAN PSIKOLOGI TERHADAP ANGGOTA POLRI DI JAJARAN POLDA JAWA TIMUR YANG MELAKUKAN PELANGGARAN DISIPLIN - Nophaz Hanggara Saputra (Jurnal Ilmu Sosial dan Humaniora, 2018)
Abstract. In the police scope, the police psychologist is typical in relation to case disclosure or case investigation, so there are some professional competences required on the psychology profession within the police. This research uses qualitative approach. The role of psychologists in the Police in terms of psychological examination related members of the police problem (violation discipline) in the East Java Police ranks is to help identify problems that lead to disciplinary action of members of the Police and assist in the form of counseling so as to reduce the disciplinary action of the Police. Where the implementation is in accordance with the Telegram Chief of Police No: Pol 292 / III / 2009 on instructions to the clauses psi pro-actively carry out guidance and counseling on a regular basis, which by examination methods through observation and in-depth interviews using humanistic approach And behavioristic. Then, the constraints of the implementation of police psychologists in terms of psychological examination related members of the police who have problems (disciplinary violations) that the lack of psychological personnel in East Java Police and personnel in the ranks still not all understand the existence of a counselor as a consultant and counselor attitudes of personnel behavior. The purpose of this study is to know and describe the role of psychologists in the police in terms of psychological examination related members of the troubled police (disciplinary offenses). Keywords: Psychologist, Counseling, Discrimination Violation Abstrak. Pada lingkup kepolisian, psikolog kepolisian bersifat khas dalam kaitannya dengan pengungkapan kasus atau penyidikan perkara, sehingga terdapat beberapa kompetensi profesi yang dipersyaratkan terhadap profesi psikologi di lingkungan kepolisian. Penelitian ini menggunakan pendekatan kualitatif. Peran psikolog di Kepolisian dalam hal pemeriksaan psikologi terkait anggota Polri yang bermasalah (pelanggaran disiplin) di jajaran Polda Jawa Timur yaitu membantu mengidentifikasi masalah yang menyebabkan tindakan indisipliner anggota Polri dan membantu dalam bentuk konseling sehingga mengurangi tindakan indisipliner anggita Polri. Dimana penyelenggaraan sudah sesuai dengan SOP yang diatur dalam Telegram Kapolri No : Pol 292/III/2009 tentang instruksi kepada para kabag psi secara pro aktif melaksanakan giat bimbingan dan Konseling secara berkala,dimana dengan metode pemeriksaan melalui observasi dan wawancara secara mendalam dengan menggunakan pendekatan humanistik dan behavioristik. Kemudian, kendala penyelenggaraan psikolog kepolisian dalam hal pemeriksaan psikologi terkait anggota polri yang bermasalah (pelanggaran disiplin) yaitu minimnya tenaga Psikolog di Polda Jatim dan personil di Jajaran masih belum semuanya memahami keberadaan konselor sebagai konsultas dan pembimbing sikap perilaku personil. Tujuan penelitian ini adalah mengetahui dan mendeskripsikan peran psikolog di kepolisian dalam hal pemeriksaan psikologi terkait anggota polri yang bermasalah (pelanggaran disiplin). Kata Kunci: Psikolog, Konseling, Pelanggaran Disiplin